Bhoodan and the landless / by K.R. Nanekar and S.V. Khandewale - "Nanekar, K.R." (Bombay, 1973)
The present work-Bhoodan and the Landless--was under taken as a part of Nagpur University's contribution to Gandhi Birth Centenary celebrations during the year 1968-69. Needless to say that Bhoodan as an application of Sarvodaya ideology is ultimately based on Mahatma Gandhi's philosophy of life and action. Bhoodan, like Sar vodaya, is more than an economic movement, and it is not easy to isolate its economic objectives from its broader social and ethical objectives. The main objective of Bhoodan is to collect lands from the landowners and distribute them among the landless, with a view to reducing disparities in landownership in rural areas.
Keywords: Bhoodan movement